Nonadherence of Polyurethane Implants: A Retrospective Cohort Study - Batiukov, Dmitry; Podgaiski, Vladimir (Indian Journal of Plastic Surgery, 2024)
Background Biointegration of polyurethane (PU) implants providing their stable position years after surgery ensures predictable results of breast augmentation and reconstruction almost eliminating implant factor as a cause of complications. However, in rare cases PU implants appear to be not connected to the surrounding tissues. The aim of the study was to determine the incidence of PU implant nonadherence after primary breast augmentations and augmentation mastopexies with dual plane implant position, to analyze possible causes, and to propose preventive measures and treatment possibilities of this complication.Methods The results of primary aesthetic surgeries in 333 patients with dual plane PU implant placement were analyzed. Patients were evaluated clinically, and pictures and videos taken in different periods after the surgery were compared. Particular attention was given to the changes in implant position and the appearance of asymmetries over time.Results PU implant nonadherence was found in seven patients. It can be divided into primary and secondary and may be complete or partial. Primary nonadherence was found in two cases (0.6%), and secondary in five (1.5%) cases. Possible influencing factors could have been traumatic surgical technique, seroma, hematoma, or physical trauma. The average follow-up was 33 months (1 month–15 years).Conclusion Biointegration is mandatory for the long-term predictable results with PU implants. PU implant nonadherence leads to implant malposition and may cause typical complications connected to non-PU implants. Improvements in surgical maneuvers, manufacturing process, and weight reduction of the implant may be beneficial for the stability of the results.Level of Evidence V
Keywords: polyurethane implants; malposition; biointegration; late seroma; capsular contracture; rotation